Sum of Arithmetic Progression/Examples/Sum of j from m to n/Proof 2

From ProofWiki
Jump to navigation Jump to search

Example of Sum of Arithmetic Progression

\(\displaystyle \sum_{j \mathop = m}^n j\) \(=\) \(\displaystyle m \left({n - m + 1}\right) + \frac 1 2 \left({n - m}\right) \left({n - m + 1}\right)\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {n \left({n + 1}\right)} 2 - \frac {\left({m - 1}\right) m} 2\)


Proof

\(\displaystyle \sum_{j \mathop = m}^n j\) \(=\) \(\displaystyle \sum_{j \mathop = 0}^n j - \sum_{j \mathop = 0}^{m - 1} j\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {n \paren {n + 1} } 2 - \frac {\paren {m - 1} m} 2\) Closed Form for Triangular Numbers